Avaliação pós-obra: estudo de caso de ciclovias através da aplicação de metodologia de inspeção - Hora, Karoline Matos da; Alvarenga, Marianna Campos; Júnior, Antonildo Campos Silva; Pereira, Claudio Henrique de Almeida Feitosa (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
The Brazilian cities have many problems associated to urban mobility. Various policies have been created to encourage the use of bicycles for all the country. Because it is a relatively new modal when compared to road pavements, it is difficult to find reliabl references regarding planning, design, execution, evaluation and maintenance for bicycle paths. This paper proposes a new evaluation methodology for rigid pavement of bicycle paths located in Brasília – DF. This evaluation is done post construction. It aims to know the pavement conditions and to help in decisions related to the maintenance phase. Besides that, it is purpose to be a parameter to the future projects. The chosen areas were called Eixo Monumental/Esplanada, Asa Norte and UnB. These places were chosen because they are older and more used. The proposed methodology approaches three phases: measurement of degradation, total damage factor survey and obtaining the cycle damage factor – FDC, this being the main objective of the work. It was possible to identify the anomalies in pavements. Finally, it was noticed that samples from the 5-year-old group were more damaged.